DYNAMICS OF ISLAMIC EDUCATION: MADRASAH TULUNGAGUNG REGENCY (1968-1984) - Muhammad Risalul Amin; Hendra Afiyanto (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
The growth of madrasas in Tulungagung Regency has contributed to the development of Islamic education in Indonesia. The existing madrasas in Tulungagung Regency do not exist just like that but go through various processes. The development of madrasas in Tulungagung Regency cannot be separated from the effects of historical events, government policies and community responses. In the early days of growth, the madrasa in Tulungagung Regency also intersected with a historic event, namely the G30 S PKI. This paper aims to provide a description of how the early development of madrasas in Tulungagung Regency. In this study, the research method used is historical research methods. Historical research methods include heuristics, verification, interpretation, and historiography. In this study it was found that the early growth of madrasas in Tulungagung Regency began around the 1950s and developed in the 1960s. The presence of madrasas in Tulungagung Regency is the result of the ideas of Muslim leaders, scholars as well as from the development of Islamic boarding school education. Madrasas play an important role in their presence in Tulungagung Regency. Apart from being a syi'ar da'wah Islam madrasa also helps eradicate illiteracy in Tulungagung Regency.